Correlation of biometric characteristics of fruits and seeds with the vigor of Agonandra brasiliensis seedlings in northern Amazonia (Bioscience Journal, 2022)
The goal of this study was to determine and correlate the main morphometric characteristics of fruits, seeds, and seedling vigor of Agonandra brasiliensis, in Roraima. The design was completely randomized with three treatments, consisting of six replications with 20 seeds. The treatments established were three classes of seeds: T1 - small seeds (S = 1.50-1.69 g); T2 - medium seeds (M = 1.70-1.89 g) and T3 - large seeds (L = 1.90-2.09 g). The variables evaluated were: length; diameter; the fresh mass of fruits and seeds; percentage, speed (in index) and average time of emergence, length of roots and aerial part; number of leaves; fresh, dry and total seedling mass; seedling lignification index; root/shoot ratio and dry root/shoot ratio and correlations between all studied variables. The fresh mass of the fruit of Agonandra brasiliensis has a high positive correlation with the mass of seeds. Small seeds of Agonandra brasiliensis exhibit a higher percentage of emergence in the conditions of the northern Amazon.